2017
DOI: 10.23956/ijarcsse/v7i2/01219
|View full text |Cite
|
Sign up to set email alerts
|

Student Performance Prediction Model using Machine Learning Approach: The Case of Wolkite University

Abstract: Abstract-A high prediction accuracy of the students' performance is helpful to identify the low performance students at the beginning of the learning process. Machine learning is used to attain this objective. Machine learning techniques are used to discover models or patterns of data, and it is helpful in the decision-making. The ability to predict performance of students is very crucial in our present education system. We applied Machine learning concepts for this study. The dataset used in our study is take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 3 publications
0
11
0
3
Order By: Relevance
“…e results show that, in small datasets, Naïve Bayes and 1-NN can perform better than decision trees [6]. Support for better performance on Naïve Bayes on smaller datasets was also shown in a study by Belachew and Gobena in [7]. e study found that the size of the dataset and the imbalance and distribution of class values are the main challenges in work obtaining better accuracies.…”
Section: Related Workmentioning
confidence: 61%
“…e results show that, in small datasets, Naïve Bayes and 1-NN can perform better than decision trees [6]. Support for better performance on Naïve Bayes on smaller datasets was also shown in a study by Belachew and Gobena in [7]. e study found that the size of the dataset and the imbalance and distribution of class values are the main challenges in work obtaining better accuracies.…”
Section: Related Workmentioning
confidence: 61%
“…They focus on the different models that previous papers have used and talked about the accuracy and process time these models had. Many papers had conflicting results as shown in how Hussain, Muhsin, Salal, Theodorou, Kurtoğlu, and Hazarika (2019) found that Neural Network models performed the best whereas Belachew and Gobena (2017) found Naïve Bayesian to be the best performing model. Belachew and Gobena's (2017) results were supported by the paper written by Jayaprakash, Balamurugan, and Chandar (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many papers had conflicting results as shown in how Hussain, Muhsin, Salal, Theodorou, Kurtoğlu, and Hazarika (2019) found that Neural Network models performed the best whereas Belachew and Gobena (2017) found Naïve Bayesian to be the best performing model. Belachew and Gobena's (2017) results were supported by the paper written by Jayaprakash, Balamurugan, and Chandar (2018). However, Obsie and Adem (2018) found that Linear Regression and Support Vector Regression were better than Neural Networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high accuracy of students" performance prediction is useful in identifying the low performing students at the start of the learning process. This objective is achieved by machine learning where techniques are employed to uncover patterns or models of data which is valuable in decision-making [12]. The study by Belachew and Gobena in [12] applied machine learning concepts to the dataset obtained from the college of www.ijacsa.thesai.org computing and informatics of Wolkite University registries office.…”
Section: Related Workmentioning
confidence: 99%